Performance in 100-km ultramarathoners - At which age, it reaches its peak? - Nikolaidis, P. T.; Knechtle, B. (The Journal of Strength and Conditioning Research, 2020)
The number of those participating in 100-km ultramarathon has increased over the past years; however, we have limited knowledge about performance trends in this sport, and particularly, the effect of age. The aim of this study was to analyze the age when women and men runners achieve their peak performance considering 1- and 5-year age group intervals, and examining all or the fastest (i.e., top 10) participants in each age group. We analyzed 370,051 athletes (i.e., 44,601 women and 325,450 men) who finished a 100-km ultramarathon between 1959 and 2016, and studied the age of peak performance using a second-order nonlinear regression analysis. The age of peak performance was 40-44 years in women and 45-49 years in men when all finishers were analyzed, whereas it was 30-34 years in women and 35-39 years in men when the top 10 finishers were considered in 5-year age groups. When we analyzed finishers in 1-year age groups, we found the age of peak performance at 41 years in women and 45 years in men considering all finishers, and at 39 years in women and 41 years in men considering the top 10 finishers. In conclusion, the age of peak performance was younger in women than in men, which might reflect the overall younger age of women participants than men. Compared with previous studies, we observed the peak performance at an age older by ~10 years, which could be attributed to an increase of finishers' age across calendar years. Because the knowledge of the age of peak performance is unique for each sport, coaches and fitness trainers might benefit from the findings of this study in the long-term training of their athletes.